Investigation of temporal profiles at the symmetrical points of the target in tissue phantoms by time-resolved fluorescence diffuse optical tomography (Withdrawal Notice) - Kitsakorn Locharoenrat (My University, 2013)
Publisher’s Note, 8 March 2017 : This paper, originally published on 7 June, 2013, was withdrawn at request of the author.
Keywords: Diffuse optical imaging; Optical Imaging and Spectroscopy Techniques